Strong Coupling Constants of the Doubly Heavy Spin-1/2 Baryons with Light Pseudoscalar Mesons. (February 2021) - Rostami, S.; Azizi, K.; Olamaei, A. R.
Abstract: The strong coupling constants of hadronic multiplets are fundamental parameters which carry information about the strong interactions among participating particles. These parameters can help us construct the hadron-hadron strong potential and gain information about the structure of the involved hadrons. Motivated by the recent observation of the doubly charmed state by LHCb, we determine the strong coupling constants among the doubly heavy spin-1/2 baryons, , and light pseudoscalar mesons, , K, and within the framework of the light cone QCD sum rules. The obtained results may help experimental groups in analysis of the related data at hadron colliders.